Characteristics of paranasal sinus osteoma and treatment outcomes. (June 2015) - Lee, Dong Hoon; Jung, Se Hee; Yoon, Tae Mi; Lee, Joon Kyoo; Joo, Young Eun; Lim, Sang Chul
Abstract Conclusion: The incidence of paranasal sinus (PNS) osteoma was 6.4%. The most common site of PNS osteoma was the ethmoid sinus. All surgically treated patients underwent endoscopic surgery, and there was no recurrence in any patient. Technical improvements, including an image guidance system, extended the indications for endoscopic surgery for PNS osteomas, especially in the frontal sinus region. Objective: The purpose of this study was to investigate the incidence and location of PNS osteomas detected by computed tomography (CT) scan at our hospital, and to describe our experience in the surgical treatment of PNS osteomas. Methods: This study was performed on 1724 patients undergoing CT scans because of suspected sinus disease between 2004 and 2013. Endoscopic surgery was performed in 34 symptomatic patients. Medical records of the patients were reviewed, and clinical findings and treatment outcomes were investigated. Results: PNS osteomas were detected in 110 patients (6.4%). Triple osteomas were detected in two patients. Double osteomas were detected in seven patients. In total, 121 lesions were identified as PNS osteomas. The ethmoid sinus was the most commonly affected site (57.0%), followed by the frontal sinus (25.6%), frontal recess (9.1%), maxillary sinus (5.0%), olfactory fissure (1.7%), and sphenoid sinus (1.7%) in descending order of frequency. Thirty-three patients were surgically treated for PNS osteomas through a purely endoscopic approach, and one patient with a frontal sinus osteoma underwent combined endoscopic surgery and frontal trephination. Image-guided surgery was performed in nine patients with involvement of the orbit and skull base, including the frontal sinus/recess. There were no major surgical complications and there was no tumor recurrence.